Balanced nutrient management for crop intensification and livelihood improvement: A case study from watershed in Andhra Pradesh, India - Chennamaneni, S.R.; Wani, S.P.; Chander, G.; Sahrawat, Kanwar Lal (Informa UK Limited, 2014)
Soil health assessment of farmers’ fields in watershed villages in Medak district, Andhra Pradesh, India showed widespread deficiencies of sulfur (S), boron (B), and zinc (Zn) in addition to organic carbon and phosphorus (P). Participatory on-farm trials on soil test-based application of deficient Zn, B, and S along with nitrogen (N) and P during 2009 to 2012 significantly increased crop yields over farmers’ practice (FP)—by 31% to 45% in chickpea, 15% to 16% in cotton, 12% to 15% in paddy, and 8% to 9% in sugarcane. Total soluble sugars in sugarcane under balanced nutrition (BN) increased by 13%. Residual benefits of S, B, and Zn were observed in succeeding chilly crop (12% higher yield). Benefit to cost (B:C) ratios of BN ranged between 2.8 to 8.5 in chickpea, 2.6 to 4.4 in cotton, 2.3 to 2.9 in paddy, and 7.1 to 11.4 in sugarcane, indicating economic feasibility for scaling-up.